Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.6564
|View full text |Cite
|
Sign up to set email alerts
|

FRI0398 Inflammatory myopathies with camptocormia or dropped head syndrome are associated scleromyositis with late onset and delayed diagnosis

Abstract: BackgroundSevere weakness of axial muscle leads to dropped head syndrome or camptocormia. The signification of these symptoms has not been studied in inflammatory myopathies (IM).ObjectivesTo assess the signification of dropped head syndrome and/or camptocormia in patients with IM.MethodsAll practitioners of the French Myositis Network and the Club Rhumatisme et Inflammation (>1000 physicians) were invited to report their patients suffering from IM (myopathy with myositis specific autoantibody and/or typical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The 27 studies included in the review consisted of seventeen non-comparative studies (nine descriptive cross-sectional studies [ 9 , 14 , 16 , 17 , 22 , 23 , 29 , 36 , 38 ], seven case reports [ 27 , 28 , 31 35 ] and one case series [ 30 ]), six analytical cross-sectional studies [ 15 , 18 – 20 , 24 , 37 ], one time series with comparison group [ 21 ] and three retrospective cohort studies [ 25 , 26 , 41 ]. Studies were from multiple countries, including nine from Europe [ 9 , 15 , 16 , 25 , 27 , 31 , 35 , 37 , 38 ], eight from the United States [ 20 , 21 , 24 , 29 , 30 , 33 , 34 , 41 ], three from Australia [ 19 , 22 , 23 ], one from New Zealand [ 14 ], two from Asia [ 28 , 32 ], and one from South America [ 26 ]. Two studies were multi-national [ 18 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 27 studies included in the review consisted of seventeen non-comparative studies (nine descriptive cross-sectional studies [ 9 , 14 , 16 , 17 , 22 , 23 , 29 , 36 , 38 ], seven case reports [ 27 , 28 , 31 35 ] and one case series [ 30 ]), six analytical cross-sectional studies [ 15 , 18 – 20 , 24 , 37 ], one time series with comparison group [ 21 ] and three retrospective cohort studies [ 25 , 26 , 41 ]. Studies were from multiple countries, including nine from Europe [ 9 , 15 , 16 , 25 , 27 , 31 , 35 , 37 , 38 ], eight from the United States [ 20 , 21 , 24 , 29 , 30 , 33 , 34 , 41 ], three from Australia [ 19 , 22 , 23 ], one from New Zealand [ 14 ], two from Asia [ 28 , 32 ], and one from South America [ 26 ]. Two studies were multi-national [ 18 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies consisting of two retrospective cohort studies [ 21 , 25 ], five cross sectional studies [ 15 , 18 , 20 , 24 , 37 ], and two non-comparative descriptive studies [ 9 , 29 ] reported the most common symptoms of their study samples. The most frequently-reported symptom was muscle weakness, reported in 8/9 studies, particularly proximal muscle weakness [ 9 , 15 , 20 , 21 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations